(3GdeaGgje(B-(3GdfeGPL(B-(3GdJWHjbGJs - (3YGOd eMehO(B, (3GdQTjOs ((3GdbGgQI(B:s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI,s, 2006)
(3jVe efWdbGJ CSGSjI, GdeOGNd GdeaGgje hGdfeGPL, GdQcGFR GdGOGQjI hGdJhLgGJ GdHGQRI aj GdTQGcI, GdeeGQSGJ hGdJLGQH GdYGdejI aj EOGQI GdTQGcI hJfXjeGJgG, ehba GdTQGcI aj GdhGbY GdYQHjs
(3HjHdjhZQGajG(B: (3U(B.215s
Keywords: (3GdTQGcIs; (3GdbWGY GdNGUs; (3GdbWGY GdYGes